2014
DOI: 10.1007/978-81-322-1979-8_11
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Finance: A Study of Correlation Between Personality Traits with the Investment Patterns in the Stock Market

Abstract: Conventional theories are based on the assumption that investors are rational beings. All their decisions are logical and judgments fair and rational. Based on this assumption, they have derived all their fi nancial models. The capital asset pricing model assumes that investors are rational beings and they have the same expectations. This assumption contradicts behavioral theories, which assume that investors under uncertainty behave in a not-so-rational or irrational manner. The phenomenon of behavioral fi na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 32 publications
4
22
1
Order By: Relevance
“…CONOPEN positively influences while agreeableness negatively affects investment performance. Generally, these consequences are similar to the research findings of Rizvi and Fatima (2015), and Nga and Yien (2013). Apparently, when making a decision on investing, investors whose personality is prone to CONOPEN produce a good result in which the return rate they achieved is as expected, and higher than previous periods as well as their satisfaction with investment decisions.…”
Section: Discussion and Recommendationssupporting
confidence: 80%
See 1 more Smart Citation
“…CONOPEN positively influences while agreeableness negatively affects investment performance. Generally, these consequences are similar to the research findings of Rizvi and Fatima (2015), and Nga and Yien (2013). Apparently, when making a decision on investing, investors whose personality is prone to CONOPEN produce a good result in which the return rate they achieved is as expected, and higher than previous periods as well as their satisfaction with investment decisions.…”
Section: Discussion and Recommendationssupporting
confidence: 80%
“…Particularly, investors are recommended to pay attention to personality traits and moods that contribute to influence on investment performance because Schwager (1993, p.49) emphasizes that "trading is emotion" and "it is mass psychology, greed and fear". Recent financial research has also shown that investors' personality is correlated to stock market investment (Cooper et al, 2000;Gherzi et al, 2014;Rizvi & Fatima, 2015) and mood takes a vital position in financial investment, even in decisions under risk and/or uncertainty (Loewenstein et al, 2001;Shu, 2010;Fenton-O'Creevy et al, 2011;Harding & He, 2015;Lepori, 2015). Apparently, there is an effect of personality traits or moods on investment performance.…”
Section: Introductionmentioning
confidence: 99%
“…Conscientiousness significantly affected investment performance. Generally, these consequences are similar to the research findings of Rizvi and Fatima (2015), and Nga and Yien (2013). Apparently, for investors possessing Conscientiousness, the more they do things efficiently, do a thorough job, plan and follow through with them, the higher their investment performance is.…”
Section: ⅴ Discussion and Recommendationssupporting
confidence: 78%
“…More specifically, their investment results are better than expected, has a high degree of safety, has lower risk compared to the market in general, has high rates of earnings growth in the past 5-10 years, has higher than average earnings projections for the next several years, and proceeds of stocks sales will be used in a way that they find productive. Notably, Rizvi and Fatima (2015) stated that all personality traits of the Big Five fully affected stock market investment in India, while Agreeableness had no direct impact on investment performance in Vietnam. These different results need to have further projects conducted and completed to validate more accurate conclusions.…”
Section: ⅴ Discussion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation